ANALISIS PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP TERHADAP KINERJA MANAJERIAL (Studi Pada Hotel Lor In di Surakarta) - Putri, Justicia Rian; Kusumawardhani, Amie (Diponegoro Journal of Management, 2017)
This research is based on the increasing of occupancy at Lor In Surakarta Hotel is not balanced with sufficient human resources. Inadequate number of employees, insufficient human resource competence, and communication systems that are often hampered by the weather result in quality of service. This study aims to examine the effect of total quality management consisting of customer focus, employee engagement and empowerment, education and training, continuous improvement, and leadership towards managerial performance.Determination of sample in research using slovin method which involves 60 respondents from all population of Hotel Lor In Surakarta. The method of analysis used in this research is multiple linear regression.The results show that customer focus, employee engagement and empowerment, education and training, and continuous improvement are positively charged to managerial performance. While the leadership proved to have no effect on managerial performance.